Peer review of the pesticide risk assessment for the active substance etoxazole in light of confirmatory data on the endocrine disruption assessment - European Food Safety Authority (EFSA); Fernando Álvarez; Maria Arena; Domenica Auteri; Sofia Batista Leite; Marco Binaglia; Anna Federica Castoldi; Arianna Chiusolo; Angelo Colagiorgi; Mathilde Colas; Federica Crivellente; Chloe De Lentdecker; et al. (EFSA Journal, 2025)
Abstract The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessment carried out by the competent authority of the rapporteur Member State Greece for the pesticide active substance etoxazole are reported. The context of the peer review was that requested by the European Commission following the submission and evaluation of confirmatory information with regard to the endocrine disruption potential of the substance. The conclusions were reached on the basis of the evaluation of the representative uses of etoxazole as an acaricide on pome fruits, plums, peaches, nectarines, apricots, cherries, citrus, grapes, strawberries, tomatoes/eggplants, cucurbits inedible peel, cotton seeds and ornamental plants. Assessments not finalised, together with the missing information identified as being required by the regulatory framework, are listed.